CHST12: a potential prognostic biomarker related to the immunotherapy response in pancreatic adenocarcinoma - Liu, Kun; Li, Lu; Han, Guang (Frontiers in Endocrinology, 2024)
Pancreatic adenocarcinoma (PAAD) is characterized by less immunogenic with a poor response rate to immune checkpoint inhibitors (ICIs) and exhibits the poorest prognosis of all solid tumors，which results in the highest tumor-related mortality among malignancies. However, the underlying mechanisms are poorly understood. In addition，diverse carbohydrate sulfotransferases (CHSTs), which involved in the sulfation process of these structures, plays an important role in metastatic spread of tumor cells. Aberrant glycosylation is beginning to emerge influencing tumor immunity and immunotherapy. Therefore, it might serve as a biomarker of immunotherapeutic response in tumors. The purpose of the study was to evaluate the role of CHST12 in PAAD prognosis and its relevance to the immunotherapeutic response.